Justice in benefitting from carbon removal - Dominic Lenzi; Hanna Schübel; Ivo Wallimann-Helmer (Global Sustainability)
Abstract Non-Technical Summary Climate stabilization requires scaling-up technologies to capture and store carbon. Carbon removal could be very profitable, and some of the agents best placed to benefit are ‘carbon majors’, i.e. fossil fuel companies. We argue that in ordinary circumstances only agents without significant historical climate responsibilities would be entitled to the full benefits from carbon removal. Under non-ideal conditions, carbon majors might be entitled to benefit, provided that no other agent could remove similar quantities of carbon at similar costs. This burden of proof is only likely to be met in countries with poor governance capacities.